Quantifying drivers of population dynamics for a migratory bird throughout the annual cycle - Rushing, Clark S. (Proc Biol Sci, 2016)
Worldwide, migratory species are undergoing rapid declines but understanding the factors driving these declines is hindered by missing information about migratory connectivity and the lack of data to quantify environmental processes across the annual cycle. Here, we combined range-wide information about migratory connectivity with global remote-sensing data to quantify the relative importance of breeding and non-breeding environmental processes to persistent long-term population declines of a migratory songbird, the wood thrush (Hylocichla mustelina). Consistent with theoretical predictions about population limitation of migratory birds, our results suggest that habitat loss and climate have contributed to the observed declines in wood thrush breeding abundance, yet the relative importance of breeding versus non-breeding factors is population-specific. For example, high-abundance core breeding populations appear to be more limited by habitat loss, whereas low-abundance, peripheral populations appear to be limited by climate-driven seasonal interactions. Further, our analysis indicates that the relative impact of breeding habitat loss is at least three to six times greater than the impact of equivalent non-breeding habitat loss and therefore the steepest regional declines have likely been driven by the loss of breeding habitat. These results underscore the need for population-specific conservation strategies implemented throughout the annual cycle to reverse long-term declines.